The importance of the general system theory for the modern world - Šijan Aleksandar; Karabašević Darjan; Rajčević Dušan (Trendovi u Poslovanju)
The paper explores General Systems Theory and its methodology. The historical development of the thought of wholeness is presented at the beginning, reflecting on philosophical attitudes that indicated the importance of the whole in relation to the parts. The paper explains how diffusion and fragmentation across scientific disciplines created needs within the science that further motivated action to create metatheory that would resolve this fragmentation and atomization through a unique - umbrella approach. The paper then gives an insight into the context of development of General Systems Theory, after which its basic premise and characteristics are presented. The following section is dealing with a specific methodology of General Systems Theory - the system approach - which includes system thinking and analysis. The ambition of General Systems Theory to form a unique new scientific paradigm is explored in the chapter focused on its contribution to contemporary science. The conclusion reveals significance of General Systems Theory, its revolutionizing on many fields and its potential limitations, but also open possibilities for further exploration.